2014
DOI: 10.1038/nbt.3103
|View full text |Cite
|
Sign up to set email alerts
|

MinION nanopore sequencing identifies the position and structure of a bacterial antibiotic resistance island

Abstract: Short-read, high-throughput sequencing technology cannot identify the chromosomal position of repetitive insertion sequences that typically flank horizontally acquired genes such as bacterial virulence genes and antibiotic resistance genes. The MinION nanopore sequencer can produce long sequencing reads on a device similar in size to a USB memory stick. Here we apply a MinION sequencer to resolve the structure and chromosomal insertion site of a composite antibiotic resistance island in Salmonella Typhi Haplot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
330
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(367 citation statements)
references
References 35 publications
14
330
3
4
Order By: Relevance
“…Both the Nanocorrect assembler described in Loman et al (53) and ABruijn assembled the ECOLInano dataset into a single circular contig structurally concordant with the E. coli K12 genome with error rates 1.5 and 1.1%, respectively (2,475 substitutions, 9,238 insertions, and 40,399 deletions for ABruijn). We note that, in contrast to the more accurate Pacific Biosciences technology, Oxford Nanopore technology currently has to be complemented by hybrid coassembly with short reads to generate finished genomes (40)(41)(42)(43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the Nanocorrect assembler described in Loman et al (53) and ABruijn assembled the ECOLInano dataset into a single circular contig structurally concordant with the E. coli K12 genome with error rates 1.5 and 1.1%, respectively (2,475 substitutions, 9,238 insertions, and 40,399 deletions for ABruijn). We note that, in contrast to the more accurate Pacific Biosciences technology, Oxford Nanopore technology currently has to be complemented by hybrid coassembly with short reads to generate finished genomes (40)(41)(42)(43).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of bacterial plankton (41), antibiotics resistance (42), and genome rearrangements (43) demonstrated that hybridSPades works well even for coassembly with less-accurate nanopore reads. Below we sketch the hybridSPAdes algorithm (40) and show how to modify the path extension paradigm to arrive at the ABruijn algorithm.…”
Section: For Details)mentioning
confidence: 99%
“…With reported features of compact, inexpensive, long read length and fast sequencing data production, the MinION device offers great potential for genome analysis from structural variation perspectives. Figure 2a shows read length profiles from two datasets, E. coli [45] and yeast [46]. In the future, it would be interesting to know how to use long reads to accurately annotate complex SVs, such as the one shown in Figure 2b, where popular SV calling tools failed using short Illumina reads.…”
Section: Emerging Technologies Of 3rd Generation Sequencingmentioning
confidence: 99%
“…A third variant, which was released by Oxford Nanopore Technologies as the MinION nanopore sequencing product, is about the size of a USB memory stick. Early literature reports on the MinION imply that it may not yet be ready for wholesale sequencing (20), but it does have some compelling applications (21).…”
Section: Genomics and Nanotechnologymentioning
confidence: 99%